Living Outside the Gender Binary: A Phenomenological Exploration into the Lived Experience of Female Masculinity - Claire, Carolyn A.; Alderson, Kevin G. (Canadian Journal of Counselling and Psychotherapy, 2012)
Individuals who express nonconforming gender identities challenge the dominant discourse in Western society, where the biological and reproductive sexed body is emphasized as the essential determinant of one’s gender identity. The purpose of this study was to explore and gain understanding of the experiences of female masculinity. Participants who have come to accept and express masculinity as an integral part of their gender identities were interviewed. Through the exploration of the participants’ experiences and reflections, 5 themes with 21 subthemes were identified that illuminate how the participants have maintained their nonconforming gender expressions despite considerable pressure to conform to gender norms. Implications for both research and counselling practice are discussed.